Validation of DYON simulations and development of physical sputtering models for lithiation and boronisation in EAST - Runze Chen; Hyun-Tae Kim; Wenbin Liu; Jinping Qian; Bin Zhang; Ximan Li; Zhengping Luo; Dalong Chen; Yaowei Yu; Wei Gao; Guizhong Zuo; Tianqi Jia; et al. (Nuclear Fusion)
This paper validates for the first time the predictive capability of the DYON code for plasma initiation in EAST, which has metallic wall, superconducting coils and conventional tokamak shape, like ITER. The model accurately reproduced the operating spaces of loop voltage and prefill gas pressure for ohmic discharges, demonstrating its validity in predicting the required operating parameters for successful inductive plasma initiation in EAST. The role of wall conditioning on plasma initiation was investigated with the newly developed physical sputtering models of Boron and Lithium. In EAST experiments, it was observed that the discharges after boronisation of the wall are much more vulnerable to plasma burn-through failure than after lithium-coating. The simulation results revealed that despite the similar physical sputtering yield in Boron and Lithium, the radiative energy loss rates for the boron-coated wall are significantly higher than those for the lithium-coated wall, due to the much higher radiative power coefficients of Boron. Parametric scans of initial Boron content in ohmic discharge at the typical prefilled gas pressure in EAST (0.8 mPa) showed that even 1.5% of Boron content in the prefilled gas, possibly remaining after boronisation of the wall, could lead to excessive radiation energy losses and failure of plasma burn-through. For successful plasma burn-through with 1.5% initial boron content, the modelling indicates 10 kW absorption of EC power is required, and it increases with more initial boron e.g. 50 kW for 3% initial boron content.